2022
DOI: 10.1021/jacs.2c03949
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Atomistic Imaging and Statistical Analysis of Daptomycin Oligomers with and without Calcium Ions

Abstract: Daptomycin (DP) is effective against multiple drug-resistant Gram-positive pathogens because of its distinct mechanism of action. An accepted mechanism includes Ca2+-triggered aggregation of the DP molecule to form oligomers. DP and its oligomers have so far defied structural analysis at a molecular level. We studied the ability of DP molecule to aggregate by itself in water, the effects of Ca2+ ions to promote the aggregation, and the connectivity of the DP molecules in the oligomers by the combined use of dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Since 3-D crystal growth comprises a series of 2-D nucleation/growth events, the mechanism described here will be pertinent to a wide variety of 3-D crystal growth processes. The present work also provides a further demonstration of the value of the cinematographic study of stochastic chemical events to access hitherto unavailable information on the interactions of molecules and ion pairs , such as molecular shuttling, C–C bond-forming reactions, and 3-D crystal nucleation recorded with millisecond angstrom resolution …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Since 3-D crystal growth comprises a series of 2-D nucleation/growth events, the mechanism described here will be pertinent to a wide variety of 3-D crystal growth processes. The present work also provides a further demonstration of the value of the cinematographic study of stochastic chemical events to access hitherto unavailable information on the interactions of molecules and ion pairs , such as molecular shuttling, C–C bond-forming reactions, and 3-D crystal nucleation recorded with millisecond angstrom resolution …”
Section: Introductionmentioning
confidence: 78%
“…Since 3-D crystal growth comprises a series of 2-D nucleation/growth events, the mechanism described here will be pertinent to a wide variety of 3-D crystal growth processes. The present work also provides a further demonstration of the value of the cinematographic study of stochastic chemical events to access hitherto unavailable information on the interactions of molecules and ion pairs 21,22 We first discuss the uncatalyzed on-site epitaxy relevant to the scheme in Figure 1b. As previously reported, the NaCl@CNT specimen was prepared by first immersing water miscible aminated CNT 24 in aqueous NaCl followed by drying in a vacuum.…”
Section: ■ Introductionmentioning
confidence: 91%
“…We initiated our investigation with PtTPP , which features the Pt in the +II oxidation state. Upon examining the substrate for pristine graphene regions at high magnifications (×2 000 000) with a moderate electron flux of ∼10 −6 e − nm −2 s −1 for SMART-EM studies, 39–44 we discovered omnipresent single Pt atoms. As highlighted in the time-dependent image sequence of two Pt atoms in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They discovered that the tetramer is the biggest oligomer in homogeneous aqueous solution, and the daptomycin molecule clusters was enhanced by the presence of Ca 2+ ions. 300 In 2016, the Schneider group investigated the biological model of daptomycin in B. subtilis, revealing that daptomycin decreased the membrane potential but no distinct membrane holes were detected during this process. They found that daptomycin affects cell wall formation whilst detecting no indication of altered membrane curvature.…”
Section: Daptomycinmentioning
confidence: 99%
“…They discovered that the tetramer is the biggest oligomer in homogeneous aqueous solution, and the daptomycin molecule clusters was enhanced by the presence of Ca 2+ ions. 300…”
Section: Biological Function Of Lipopeptides From Streptomyces As Ant...mentioning
confidence: 99%